The measurement of service quality using SERVQUAL: the case study of Peladang Setiu Agro Resort, Terengganu, Malaysia. - Rosliza Che Rahim; WM. Nazdrol WM.Nasir
This article examines the measurement in the context of the previous instrument (SERVQUAL) in measuring the service quality. SERVQUAL is an instrument developed by Parasuraman, Zeithaml and Berry (1985), is currently the most popular measurement of service quality. In this article, SERVQUAL was used to measure the service quality at Peladang Setiu Agro Resort which is located at Terengganu, Malaysia.The main objective of this study is to determine whether there is a gap exists between the perception and the expectation of visitors on selected dimensions such as tangibility, reliability, responsiveness, assurance and empathy. The data was collected using selfadministrated questionnaires and the findings shows that there is a significant gap between the perceptions and expectations of the service quality among the respondents. As a result, this paper also provides some recommendation that aim to assist the service provider in minimizing the gap between the perception and expectation; and hence fulfill the expectation of the tourists that stay at Peladang Setiu Agro Resort.